PENGARUH KEPEMILIKAN INSTITUSIONAL, LEVERAGE, POLITICAL COST, SIZE, DAN GROWTH TERHADAP KONSERVATISME AKUNTANSI - AZIF ARSANTO, YOGA (Jurnal Akuntansi AKUNESA, 2017)
This research examines the effect of institutional ownership, leverage, political cost, size, and growth to the accounting conservatism. This research is motivated by a phenomenon where the principle of conservatism in accounting is still disputed and many factors affect the application of conservatism. Using quantitative and regression model on listed companies at Indonesia Stock Exchange that consistently apply conservatism during 2011-2015, this research finds that leverage and size have a positive effect on accounting conservatism. However, institutional ownership, political cost, and growth are not significantly influence accounting conservatism. Keyword: accounting conservatism, growth, leverage, size